2018
DOI: 10.1002/asjc.1935
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Derivative Control on SIPIC in Motor Speed Control

Abstract: The proportional–integral–derivative (PID) controller is the most commonly used controller in control application due to its simplicity. However, the control output may exceed the plant input limit which eventually deteriorates the system performance. This is known as a windup phenomenon, which causes large overshoot, long settling time and instability in the control system. Various anti‐windup methods have been introduced to overcome the windup phenomenon such as the Steady‐State Integral Proportional‐Integra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…This controller avoids the integral windup problem and suppresses the derivative kick. Choon Lih Hoo et al [ 18 ] discussed the effect of integrating derivative control on the Steady-State Integral–Proportional–Integral Controller (SIPIC) in motor-speed control. The experimental results showed that the SIPIC + D controller has better speed control on a direct current motor compared with other existing anti-windup methods with added derivative control.…”
Section: Introductionmentioning
confidence: 99%
“…This controller avoids the integral windup problem and suppresses the derivative kick. Choon Lih Hoo et al [ 18 ] discussed the effect of integrating derivative control on the Steady-State Integral–Proportional–Integral Controller (SIPIC) in motor-speed control. The experimental results showed that the SIPIC + D controller has better speed control on a direct current motor compared with other existing anti-windup methods with added derivative control.…”
Section: Introductionmentioning
confidence: 99%
“…The SIPIC and SIPIC02 were built without the need of switching mechanism. SIPIC [13,14] has a decoupling feature that enables individual tuning effect of the controller proportional gain, k p and integral gain, k i on the system. This is done by separating the two gains in the dynamical mathematical model.…”
Section: Introductionmentioning
confidence: 99%